The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1038/aja.2011.153
|View full text |Cite
|
Sign up to set email alerts
|

Influence of paradoxical sleep deprivation and sleep recovery on testosterone level in rats of different ages

Abstract: This study was performed to assess serum testosterone alterations induced by paradoxical sleep deprivation (PSD) and to verify their attenuation during sleep recovery (SR) based on different durations and ages. Wistar male rats aged 12 weeks for the younger group and 20 weeks for the elder group were randomly distributed into one of the following groups: a control group (cage and platform), 3-day SD, 5-day SD, 7-day SD, 1-day SR, 3-day SR and 5-day SR groups. For PSD, the modified multiple platform method was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 29 publications
1
15
0
1
Order By: Relevance
“…Previous animal studies simulating sleep deprivation have shown that sleep interruption significantly interrupts with the circadian rhythm of testosterone. 16 Groups of younger and older rats were kept in a sleep deprived state by placing them within a modified disk-over-water chamber, resulting in a significant decrease of testosterone in the older rats. Clinical studies on sleep disruption have also shown a significant relationship between the disruptions of nocturnal testosterone rhythm and sleep fragmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous animal studies simulating sleep deprivation have shown that sleep interruption significantly interrupts with the circadian rhythm of testosterone. 16 Groups of younger and older rats were kept in a sleep deprived state by placing them within a modified disk-over-water chamber, resulting in a significant decrease of testosterone in the older rats. Clinical studies on sleep disruption have also shown a significant relationship between the disruptions of nocturnal testosterone rhythm and sleep fragmentation.…”
Section: Discussionmentioning
confidence: 99%
“…The MMPM, illustrated elsewhere [ 23 , 25 ], was selected to build the CSD model in this study. Rats from the CSD group were group housed (six rats in each arena) in modified multiple platform arenas during periods of sleep deprivation.…”
Section: Methodsmentioning
confidence: 99%
“…The CSD rats were intervened by the modified multiple platform method (MMPM), which was proved available to build the CSD model [ 26 ]. The animals were group housed (six rats in each arena) in modified multiple platform arenas during CSD.…”
Section: Methodsmentioning
confidence: 99%